Determination of Diagnostic Accuracy of Aspartate Aminotransferase/Alanine Aminotranferase in Patients with Hepatic Cirrhosis Presented at Tertiary Care Hospital of South Punjab Pakistan - Younas, Amna; Hanif, Waqas; Sheikh, Muhammad Ali Ahmad; Younas, Muhammad; Ellahi, Sana; Ain, Qurat ul (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the diagnostic accuracy of Aspartate aminotransferase/Alanine aminotransferase ratio in hepatic cirrhosis keeping liver biopsy as a reference standard. Study Design: Cross-sectional analytical study. Place and Duration of Study: Department of Medicine, Nishtar Hospital, Multan and Combined Military Hospital, Multan Pakistan, from Dec 2019 to Mar 2020. Methodology: Two hundred and fifty (250) patients were consecutively picked according to inclusion and exclusion criteria after approval of the institutional review board. Blood Samples were collected from patients for serum alanine aminotransferase and serum aspartate aminotransferase after informed consent who had undergone liver biopsy and Batt Ludwig was the staging system used to stage liver cirrhosis. They were interpreted at Nishtar Hospital Multan Pakistan and analyzed in Combined Military Hospital Multan Pakistan by using the Spectrophotometry technique by IFCC certified enzymatic method. Aspartate aminotransferase/Alanine aminotransferase ratio was derived which represents hepatic cirrhosis keeping liver biopsy as a reference standard. Result: 230 patients out of 250, fulfilled the inclusion criteria. Kolmogorov smirnov test showed data is non-parametric. The Aspartate aminotransferase/Alanine aminotransferase ratio for diagnosing hepatic cirrhosis in patients with hepatic cirrhosis, its sensitivity, specificity, negative predictive value, positive predictive value and accuracy were 72%, 68%, 89%, 41%, and 69% respectively. The receiver operating curve proclaims that Aspartate aminotransferase/Alanine aminotransferase of 1.7 with an area under the curve was 0.795 which is consistent with histopathological findings of hepatic cirrhosis in liver biopsy. Conclusion: To conclude, Aspartate aminotransferase/Alanine aminotransferase may be wielded as an incredible diagnostic tool for patients suffering from viral...